Observation of Kelvin–Helmholtz billows in the marine atmospheric boundary layer by a ship-borne Doppler wind lidar - Shokoufeh Malekmohammadi; Etienne Cheynet; Joachim Reuder (Scientific Reports)
Abstract Kelvin–Helmholtz billows (KHB) and the associated turbulence characteristics in the atmospheric boundary layer (ABL) are mainly investigated through simulations and limited observations. Traditional methods using in-situ wind sensors are constrained by mast height, resulting in a limited understanding of KHBs at higher altitudes. Lidar remote sensing provides a promising approach for studying KHBs at altitudes above 100 m. This study presents observations of KHBs in the marine ABL above 600 m, through ship-borne lidar observations. Two Doppler wind lidars, one scanning lidar, and one wind profiler, were installed for several months on a crew transfer vessel, operating in the Rødsand 2 wind farm off the coast of Denmark. On 2023-02-22, KHBs were detected between 600 and 800 m altitude over 10 min. The standard deviation of vertical turbulence was found to increase by a factor of two during KHB occurrence. The power spectral density of vertical fluctuations showed a greater increase in the frequency range below 0.1 Hz, with a peak indicating a periodic pattern with a period of 55 s. The kurtosis of the vertical component also showed a large increase near the edge of the billows, as documented in the scientific literature for billows occurring near the surface. The billows triggered a downward mixing of aerosols and momentum to around 550 m. Although no interaction between the wind farm and the KHBs was observed, we hypothesise that KHB may reduce wind farm wake losses in shallower stable layers above the farm by enhancing vertical mixing and downward momentum transport.